PENGARUH DOSIS URINE SAPI TERHADAP PERTUMBUHAN BIBIT TREMBESI (Samanea saman) - Malwani, Fanny; Rosianty, Yuli; Lensari, Delfy (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2014)
The purpose of the study were: 1 ) to determine the best dose of cow urine is used as a liquid organic fertilizer in the seedling growth Trembesi ( Samanea saman ) in poly bags. This research was conducted in the area of land home page . On the road. Manuscript Km 7 , District No. Sukarami . 23 . The timing of the start in April to July 2013. Methods of observation in this study using a randomized block design (RBD) Non Factorial with cow urine fertilizer treatments consisting of D0 = 0 ml (control) , D1 = 25 ml cow urine / 500 ml of water / plant , D2 = 50 ml cow urine /500 ml of water / plant , D3 = 75 ml cow urine / 500 ml of water / plant , and D4=100 ml of cow urine / 500 ml of water / plant . The results showed that treatment of cow urine fertilizer very significant effect on plant height , diameter , number of leaves , number of branches and root length of seedlings Trembesi . Conclusions based on the results of the study that a dose of 75 ml of cow urine / 500 ml of water/plant gives best results on seedling growth Trembesi , relating to the cultivation of plants Trembesi maintained its sustainability .